THE INFLUENCE OF COACHING-BASED ACADEMIC SUPERVISION ON TEACHER PERFORMANCE AT SMA NEGERI 1 AMURANG AND SMA NEGERI 1 MOTOLING - Liow, Swingly Suriadi Yesaya; Lengkong, Jeffry S.J; Katuuk, Deitje A. (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the influence of coaching-based academic supervision on teacher performance at SMA Negeri 1 Amurang and SMA Negeri 1 Motoling. The study employed a quantitative approach with an explanatory design. The population consisted of 122 teachers, all of whom were included as the sample using a saturated sampling technique. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis included descriptive analysis, prerequisite tests, and simple linear regression. The results showed that coaching-based academic supervision does not have a significant effect on teacher performance (p > 0.05). The coefficient of determination (R²) value of 0.013 indicates that the contribution of coaching-based academic supervision to teacher performance is very low, accounting for only 1.3%, while most of the variation in teacher performance is influenced by other factors outside the research model. These findings indicate that coaching-based academic supervision has not been able to directly improve teacher performance, especially when its implementation is not carried out consistently and in depth. This study emphasizes that the effectiveness of coaching-based supervision is contextual and highly dependent on the quality of implementation and the support of the school’s organizational environment.